Associations of the IL‐1F7 gene polymorphisms with rheumatoid arthritis in Chinese Han population. (21st November 2012) - Pei, B.; Xu, S.; Liu, T.; Pan, F.; Xu, J.; Ding, C.
Summary Our aim was to investigate whether genetic polymorphism of IL‐1F7 (rs3811047) was involved in the susceptibility to rheumatoid arthritis (RA) in Chinese Han population. Single nucleotide polymorphism (SNP) of IL‐1F7 gene (rs3811047) was analyzed in 184 unrelated Chinese Han patients with RA and 184 healthy controls by ligase detection reaction based on high temperature ligase detection reactions polymerase chain reaction (LDR‐PCR). There were no statistically significant differences in the genetic polymorphism (genotypes and allele frequencies) of IL‐1F7 (rs3811047) in the patients with RA compared with control. Although all of the clinical and laboratory measures were similar to each other among patients with different genotypes, RA patients carrying AA or AG genotypes had lower swollen joint count, swollen joint index, rest pain and health assessment questionnaire (HAQ) score than that in patients having GG genotype (P < 0.05). These findings show that no evidence for the involvement of a pro‐inflammatory polymorphism in the IL‐1F7 in the susceptibility to RA in China. Patients carrying A allele had less severe disease activity than those not carrying this allele, suggesting that the A allele of IL‐1F7 gene (rs3811047) may have a protective effect on RA.